Analisa Penerapan Sensor Detak Jantung Pada Teknologi Virtual Reality Terapi Acrophobia - Hidayat, Kardilah Rohmat; Setyanto, Arief; Sadikin, Moh. Fal (Politeknik Indonusa Surakarta, 2022)
Fear of heights can also be called acrophobia, which is to have a very excessive fear of heights. The fear experienced by acrophobia sufferers causes the effects of symptoms, including anxiety, panic, and stress, when in a high area. To treat phobia of heights is not so easy, but it can be overcome by conducting therapy. One of the therapies carried out is exposure which is an effective therapeutic medium in overcoming acrophobia. In this study, an analysis was carried out using the pretest-posttest control group method for VRET (Virtual Reality Exposure Therapy) validation as well as a comparison method between the products developed and products on the market for validation of heart rate sensors. The results showed that VRET (Virtual Reality Exposure Therapy) is effective in lowering individual perceptions of changes in physiological reactions experienced related to altitude situations and the heart rate sensor module can be used for Virtual Reality Acrophobia applications. The use of a heart rate sensor is recommended on the left hand because research shows a small difference in accuracy between the heart rate sensor and the Oxymeter.